2016
DOI: 10.4292/wjgpt.v7.i2.261
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with visceral fat accumulation in the general population in Okinawa, Japan

Abstract: AIM:To investigate the clinical and biochemical factors associated with visceral fat accumulation in the general population. METHODS:We enrolled 1004 subjects who underwent a medical health checkup between April 2008 and March 2009. The medical health checkup included the following tests: Height, body weight, waist circumference (WC), systolic blood pressure, diastolic blood pressure, urinalysis, blood-cell counts, blood chemistry, electrocardiography, chest radiography, and abdominal computed tomography (CT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…These findings were consistent with previous studies [ 48 , 49 , 50 , 51 ]. We suggested that the high levels of visceral fat, percentage of body fat, fat mass, fat-free mass, muscle mass, total body water, bone mass and basal metabolic rate in males may be associated with sex hormones, alcohol consumption, smoking, nutritional intake and physical activity [ 52 ]. Furthermore, in females, estrogen hormones may direct the expansion of fat through an increase in adiposity progenitor cells, affecting the percentage of fat in females more than in males [ 45 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with previous studies [ 48 , 49 , 50 , 51 ]. We suggested that the high levels of visceral fat, percentage of body fat, fat mass, fat-free mass, muscle mass, total body water, bone mass and basal metabolic rate in males may be associated with sex hormones, alcohol consumption, smoking, nutritional intake and physical activity [ 52 ]. Furthermore, in females, estrogen hormones may direct the expansion of fat through an increase in adiposity progenitor cells, affecting the percentage of fat in females more than in males [ 45 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, increasing hemoglobin level was associated with increasing arterial stiffness, which is used to assess CVD in high-risk populations [ 10 ]. Also, higher hemoglobin concentrations are present in individuals with metabolic syndrome or insulin resistance versus healthy controls or obese subjects versus non-obese subjects [ 11 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The excessive accumulation of visceral adipose tissue (VAT) leads to visceral obesity and induces low-grade systemic inflammation, which is mediated by fat-infiltrating immune cells and increased release of proinflammatory cytokines [ 1 4 ]. Although the exact mechanisms that initiate VAT accumulation have not been fully elucidated, it is generally believed that excess VAT is closely associated with the development of a cluster of metabolic derangements, hypertension, cardiovascular disease, and malignancies.…”
Section: Introductionmentioning
confidence: 99%